Exploring the association between dental caries and body mass index in public school children of Ahmedabad city, Gujarat - Sujal Mitul Parkar; Mansi Chokshi (Wolters Kluwer Medknow Publications, 2013)
Objective: The aim of this study is to assess whether dental caries was related to body mass index (BMI) in school going children of Ahmedabad city (Gujarat), India. Materials and Methods: Dental and anthropometric examinations were conducted on 750 school going children with a mean age of 10.96 ± 3.14 years from ten public schools. Dental caries was diagnosed according to World Health Organization (WHO) criteria using deft/decayed, missing and filled teeth (DMFT) index. Nutritional status was obtained using BMI and classification of nutritional status was achieved using the standards of WHO. Results: Out of the 750 children, 450 (60%) were male and 300 (40%) were female. There was a highly significant difference (P < 0.001) when the prevalence of dental caries (deft/DMFT) was compared in different age groups of children. About 653 (87.1%) out of 750 children were underweight. There was a highly significant difference (P < 0.001) when the BMI and mean deft score was compared; however, when the BMI and mean DMFT score was compared the result was not reached to the significant level (P > 0.05). Significant correlation (P < 0.001) was observed between the different age groups and caries. There was a negative correlation between deft and BMI showing a significant result. Conclusion: Increase in age and underweight children were more likely to have caries experience.